Digital Cloud Storage: The Best Cloud Drive Analysis for Digital Business Purposes - Irham Khairul Muttaqin; Lanina Astrid; Aditya Akbar Prasetyo; Nabilah Fitria Kamaludin; Azizah Ghina (Indonesian Journal of Digital Business, 2021)
The economy has been transforming throughout the years, and internet development has brought something new into the business world. With the rapid grown of technology, the economy and technology are inseparable. E-commerce was an example of an economy and technology. A huge data stream needed to be stored, and make physical storage now is outdated. Cloud storage was the option for storing and securing the company data. It has many benefits for the company for using cloud storage. The research methods in this paper was a literature research journal review. By comparing various cloud storage, it was found that mega cloud storage was a suitable option for many businesses from our related journal and other literature. Mega was encrypted and can store many data stream safely that the company needed.